Pengaruh Kreativitas terhadap Inovasi dan Kinerja Pemasaran pada Pengusaha Kerajinan Bambu di Kabnpaten Jember - Asmuji Asmuji (Jurnal Aplikasi Manajemen, 2010)
Agroindustry as one of agribusiness system sub has important role in movement of national economy activity. Besides, role of agroindustry especially having location in rural is to increase industry earnings, as well as increasing quality than it self agricultural produce. This research is aim (1) to analyze and test creativity influence to revenues innovation on industry brass company Bamboo Handycaraf in Jember Regency. (2) to analyze and test creativity influence to revenues marketing performance on industry brass company Bamboo Handycaraf in Jember Regency. (3) to analyze and lest innovation influence torevenues marketing performance on industry brass company Bamboo Handycaraf in Jember Regency. Method applied in this research is survey research by using questionnaire as a means of data colleting Research subject is the lead of industry brass company. Simultaneo usly testing by using Path Analyze Obtained that selling Creativity, Innovation, Marketing Performance . This research will be to give an answer difference this research.